1995
DOI: 10.1002/ange.19951072124
|View full text |Cite
|
Sign up to set email alerts
|

Metallkomplexe heterocyclischer Carbene ‐ ein neues Katalysator‐Strukturprinzip in der homogenen Katalyse

Abstract: Durch „Carben”︁‐Donorliganden stabilisiert ist der Pd‐Komplexe 1, der die Heck‐Olefinierung von Arylhalogeniden unerwartet effizient katalysiert. Die aktive Pd0‐Spezies kann man gezielt durch Reduktion von 1 oder auch in situ aus Pd0‐Komplexen und 1,3‐Dimethyldihydroimidazol‐2‐yliden erhalten. Der von Imidazol abgeleitete „Carben”︁ ‐Ligand, der treffender als C‐basischer Donorligand zu formulieren ist, macht den erstmals hergestellten Komplex 1 zu einem auch bei hohen Reaktionstemperaturen langzeitstabilen Kat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
117
0
15

Year Published

1998
1998
2005
2005

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 245 publications
(136 citation statements)
references
References 20 publications
4
117
0
15
Order By: Relevance
“…Besides the expected square-planar core geometry, a crystal structure analysis of 1 revealed that the two carbene ligands are in a trans arrangement and are coplanar with respect to the PdI 2 plane. The Pd-C bond lengths [2.01(4)/ 2.06(3) Å ] lie within the established range for Pd-C(alkyl) single bonds, [16] although the 13 C-NMR signal of the car-bene C appears further downfield (δ ϭ 210.5) than the corresponding signals of imidazole and triazole carbenes (δ ϭ 169-185); [3][4][5] this is in accordance with the values found for the stable N-diisopropylphenylthiazole carbene. [12] From an XPS analysis of 1, a binding energy of 337.2 eV was determined, which is very close to the value of 337.0 eV typical for Pd II .…”
Section: Resultsmentioning
confidence: 96%
See 2 more Smart Citations
“…Besides the expected square-planar core geometry, a crystal structure analysis of 1 revealed that the two carbene ligands are in a trans arrangement and are coplanar with respect to the PdI 2 plane. The Pd-C bond lengths [2.01(4)/ 2.06(3) Å ] lie within the established range for Pd-C(alkyl) single bonds, [16] although the 13 C-NMR signal of the car-bene C appears further downfield (δ ϭ 210.5) than the corresponding signals of imidazole and triazole carbenes (δ ϭ 169-185); [3][4][5] this is in accordance with the values found for the stable N-diisopropylphenylthiazole carbene. [12] From an XPS analysis of 1, a binding energy of 337.2 eV was determined, which is very close to the value of 337.0 eV typical for Pd II .…”
Section: Resultsmentioning
confidence: 96%
“…[12] From an XPS analysis of 1, a binding energy of 337.2 eV was determined, which is very close to the value of 337.0 eV typical for Pd II . It may therefore be the case that benzothiazole carbenes have pronounced σ-donor properties similar to those of imidazole carbenes [3] and that π-back-bonding is probably less significant than that seen with the electronrich phosphanes.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…In addition, unreactive arylating agents like aryl chlorides can be used. More variations on this theme are the use of bulky phosphite (18,41) or phosphoramidite ligands (42), carbene ligands (43,44), and pincer ligands (31,45). Another interesting, cheap, and very active class of catalysts are the palladacycles based on aromatic compounds with side chains containing N (41,46), O (47), or S (48,49).…”
Section: Development Aspectsmentioning
confidence: 99%
“…phosphane, amine, alkoxy, Schiff base), substituent group manipulations allow fine-tuning of the steric and electronic properties of the NHC ligand thus conferring special attributes to the metal complex. 5 Most NHCs have turned out to be quite efficient ancillary ligands in transition metal complexes widely used as highly active and rather selective catalysts (or precatalysts) in numerous fundamental chemical transformations such as hydrogenation, 6 hydrogen transfer, 7 hydroformylation, 8 hydrosilylation, 9 isomerization, 10,11 telomerization, 12 Kharash addition, 13 Pauson-Khand cyclization, 14 olefin metathesis 15 and various C-C coupling reactions. [16][17][18] Of these catalytic processes, olefin metathesis has recently undergone spectacular development, becoming a powerful synthetic protocol in organic and polymer chemistry.…”
Section: Introductionmentioning
confidence: 99%